MEMAHAMI PENTINGNYA MENJAGA ASUPAN MAKANAN SEHAT DENGAN MODEL PEMBELAJARAN COOPERATIVE TiIPE NUMBER HEAD TOGETHER (NHT) - Dwiba Elisa; Siti Alimah; Sri Sulistiyorini (Profesi Pendidikan Dasar, 2019)
The purpose of this study was to improve the activity and cognitive learning outcomes of students using the NumberT Together Learning Model (NHT) Cooperative. The research methodology used is quantitative pre-experimental research with research design using a one-time case study. The data obtained in this study were data from pretest and posttest. The data analyzed to see the score of the test results. Then the test results are calculated on average and calculate the N-Gain between the pretest and posttest. The learning process using cooperative learning model Number Head Together (NHT) seen from the results of pretest 67.142 and posttest results 77.142 shows a 10% increase in student learning outcomes in the medium category with N-Gain value 0.304. While based on the results of the learning done, the cooperative learning model Number Head Together (NHT) increases student learning activities by 30% from 55% to 85%.